Morfologi Bahasa Arab: Reformulasi Sistem Derivasi dan Infleksi - Muhammad Aqil Luthfan; Syamsul Hadi (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2019)
Morphology, in the study of Arabic linguistics known as the discipline ‘ilm al-ṣarf, as part of grammar which examines the internal structure of words, has an urgency to be studied in depth. Especially in the context of Arabic studies that embrace typologies of complex inflective languages. This article examines the Arabic morphological system from a modern linguistic perspective, especially on derivational and inflectional changes. The discussion begins on the conception of derivation and inflection in the view of modern linguistics, as an introduction to see the system of derivation and inflection changes in Arabic linguistics. Morphological theories of Arabic grammars, in this article developed and communicated with modern linguistic theories. From this development a new formula was produced in the study of Arabic morphology which is expected to provide a more systematic description of the understanding of the Arabic morphological system.